Studi Kasus Kecurangan Akuntansi Pada Koperasi Mitra Jaya Kelurahan Penarukan Kecamatan Buleleng (Suatu Kajian Terhadap Pentagon Crowy) - Larasati, Riska; Sujana, Edy (Universitas Pendidikan Ganesha, 2021)
This study aims to obtain empirical evidence about accounting fraud in the Cooperative Mitra Jaya Kelurahan Penarukan Buleleng District from the perspective of pressure, opportunity, rationalization, competency, and arrogance. This research is a descriptive qualitative research. The data used in this study are primary data and secondary data. The results of this study indicate that: (1) Fraud conducted by Mitra Jaya Cooperative can be seen from the aspect of pressure, such as the existence of debt, luxury lifestyle to debt which is not in accordance with the loan agreement, resulting in bad credit that results in cooperative capital to impact on the division of SHU at the end of the year. (2) Fraud conducted by Koperasi Mitra Jaya is seen from the aspect of opportunity, among others, because it is supported by situations and conditions that enable someone to cheat or an opportunity to manipulate financial and personal data related to loan applications. (3) Fraud conducted by Mitra Jaya Cooperative can be seen from the aspect of rationalization, among others because the attitude of the perpetrators who are looking for reasons to justify the crime they have committed so that it can be accepted by the community. (4) Fraud conducted by Mitra Jaya Cooperative is seen from the aspect of competency, among others because the actor has the ability to override internal control and control it in accordance with his social position for his personal interests. (5) Fraud conducted by Mitra Jaya Cooperative is seen from the aspect of arrogance which is an attitude of superiority and greed in a person who considers that company policies and procedures simply do not apply personally so that the perpetrators are free to commit fraud.